Analisis Sikap Siswa Sekolah Dasar terhadap Nilai Kesopanan dalam Pembelajaran Pendidikan Pancasila - Pramawati, Annisa Maghfira; Suntari, Yustia; Yudha, Chrisnaji Banindra (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2025)
Character education – especially in the context of politeness values ​​– is very important to be implemented from an early age. This study aims to analyze students' attitudes towards politeness values ​​and the factors that influence them in the learning process of civic education. This study uses a qualitative approach with data collection techniques in the form of non-participatory observation, interviews, and documentation. The subjects of this study were 32 fifth grade students at SDN Cipedak 05, South Jakarta. The results of the study indicate that students have generally applied politeness values ​​in learning civic education. However, there is one aspect that has not been reflected optimally, namely speaking well to peers. Factors that influence politeness values ​​in students' attitudes are school, family background, and social environment. With this, it can be said that politeness values ​​in students' attitudes are generally good, it only requires active cooperation from the school, parents, and social environment to be able to build good habits related to politeness values.